Spatial variability of soils and stream sediments and the remediation effects in a Portuguese uranium mine area - Neiva, Ana Margarida Ribeiro (2016)
The old Senhora das Fontes uranium mine, located in central Portugal, was closed down in 1971. Thetreatment of ores from this mine and other mines by heap-leach ended in 1982. Seven dumps partiallycovered by vegetation were left in the area. Soil and stream sediment samples were collected in December2009. The remediation was carried out from May 2010 to January 2011. Stream sediment samples werecollected again in October 2013. Before the remediation, soils from inside the mine influence area havehigher Al, As, Co, Cr, Cu, Fe, Ni, Sr, Th, U and Zn concentrations than soils from outside this area, due toradionuclides, metals and metalloid released from the mine dumps. The principal component analysis(PCA) shows a distinction between soils from inside and outside the mine influence area. The U(VI),As(V) and metals from soils can be adsorbed to Fe-oxyhydroxides and the humic acid can increase theU uptake. Soils must not be used for public or private green and residential areas, because they arecontaminated in U, As, Co, Cd and Ni. Before the remediation, downstream sediments have higher Al, As,Cu, Mn, Ni, Pb, U and Zn than upstream sediments, due to erosion and percolation of water through themine dumps. The PCA shows a distinction between downstream and upstream sediments. The U(VI), Thand As(V) can be adsorbed to Fe-oxyhydroxides. The stream sediments are contaminated in As, Mn, Thand U. Downstream sediments are the most contaminated in U and As. After the remediation, upstreamand downstream sediments have generally higher Al, Fe, As, Cr, Ni, Th, U and Zn concentrations thanbefore the remediation, attributed to the relocation of dumps. Radionuclides, metals and metalloidswere transported by surface water. Consequently downstream sediments have higher Al, As, Cu, Mn,Ni, Th, U and Zn concentrations than upstream sediments. The U(VI), Th and As(V) can be adsorbedto Fe-oxyhydroxides. Stream sediments became more contaminated in U, Th and As than before theremediation, but more intensively downstream.